1997
DOI: 10.1093/hmg/6.8.1275
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-dependent diabetes mellitus (IDDM) is associated with CTLA4 polymorphisms in multiple ethnic groups

Abstract: Linkage disequilibrium (association) analysis was used to evaluate a candidate region near the CTLA4/CD28 genes using a multi-ethnic collection of families with one or more children affected by IDDM. In the data set unique to this study (Spanish, French, Mexican-American, Chinese and Korean), the transmission/disequilibrium test (TDT) revealed a highly significant deviation for transmission of alleles at the (AT)n microsatellite marker in the 3' untranslated region (P = 0.002) and the A/G polymorphism in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
237
5
6

Year Published

1999
1999
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(259 citation statements)
references
References 37 publications
11
237
5
6
Order By: Relevance
“…This result is consistent with the absence of association of this marker with T1D in West Africans 21 and Asians. 11,13,19 The absence of association between different alleles of the dinucleotide (AT) repeat and the level of CTLA4 expression as well as the stability of CTLA4 mRNA has been reported. 25 Therefore, the differences of frequencies found for the smallest allele (allele 7) of the (AT) n repeat in our population and the previously observed association between T1D and longer alleles may be the result of LD between specific microsatellite alleles and the true etiological factor of susceptibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with the absence of association of this marker with T1D in West Africans 21 and Asians. 11,13,19 The absence of association between different alleles of the dinucleotide (AT) repeat and the level of CTLA4 expression as well as the stability of CTLA4 mRNA has been reported. 25 Therefore, the differences of frequencies found for the smallest allele (allele 7) of the (AT) n repeat in our population and the previously observed association between T1D and longer alleles may be the result of LD between specific microsatellite alleles and the true etiological factor of susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16] Nevertheless, in other studies with populations of European ancestry, no evidence of association was found. [17][18][19][20] Recently, an association with a novel polymorphism at position 159 has been found in West African populations, but not in Chinese. And conversely, the CTLA4+49 (A-G) marker conferred a risk of T1D in Chinese but not in west Africans.…”
Section: Introductionmentioning
confidence: 99%
“…IDDM12 was mapped by linkage (MLS 3.2), and by association with CTLA4 in Italian and Spanish datasets (combined p value 0.0001) but not in American, British or Sardinian datasets [76]. It was confirmed by demonstration of highly significant association with an A/G (Thr/Ala) polymorphism in exon 1 of CTLA4 in 669 multiplex and 357 simplex families (p = 0.00 005) [77]. Again, there was marked population heterogeneity for this association: Italian, Spanish, French, Mexican, and Korean samples showed significantly increased transmission of the G allele to diabetics, while British, Sardinian, Chinese, and European-Americans showed little or no increased transmission of this allele.…”
Section: Is Positional Candidate Mapping Feasible?mentioning
confidence: 92%
“…The insulin gene (INS; IDDM2) and the cytotoxic T-lymphocyteassociated protein 4 (CTLA4) gene regions (IDDM12) are considered as confirmed non-HLA disease susceptibility loci [12][13][14][15][16]. Short (class I) alleles of the insulin gene 5′ variable number of tandem repeats (VNTR) are associated with increased type 1 diabetes susceptibility fitting an allele dosage model, while long class III alleles confer protection [17].…”
Section: Introductionmentioning
confidence: 99%
“…Short (class I) alleles of the insulin gene 5′ variable number of tandem repeats (VNTR) are associated with increased type 1 diabetes susceptibility fitting an allele dosage model, while long class III alleles confer protection [17]. In the CTLA4 region, a number of variants, like the +49A/G, have shown disease association in various ethnic groups, while the CT60 polymorphism was identified as a candidate causative disease variant [14][15][16]18].…”
Section: Introductionmentioning
confidence: 99%